Leadership Strategies of the Head of Madrasah in Enhancing the Effectiveness of Educational Administration at Madrasah - Muhammad Khoirul Anam; Nurma Ifada; Siti Miftah Mustofiyah; Abdussalam; Muhammad Anwar Fuadi; Ahmad Isa Tranjaya (Al-Qalam Institue, 2026)
This study aims to describe and analyze the role of the head of madrasah in optimizing educational administration, with a particular focus on the transition toward digital administration at MTs Miftahul Jannah Mantingan, Ngawi. This research employed a descriptive qualitative method using a case study approach. Data were collected through observations, in-depth interviews, and documentation, involving key informants consisting of the head of madrasah, vice principal for curriculum, administrative staff, and teachers. The findings reveal that the head of madrasah plays a strategic role as an administrator, manager, supervisor, and motivator in driving administrative transformation. The madrasah has initiated digitalization by utilizing Google Spreadsheet and Google Form, as well as specialized applications such as the Madrasah Budget Plan (RK) and Digital Madrasah Report (RDM), particularly in financial administration. This transition has resulted in improved work efficiency and positive responses from students’ parents. However, several challenges persist, including limited internet infrastructure, financial constraints, and inadequate human resources with sufficient digital competencies. The study implies that the optimization of educational administration is highly dependent on visionary leadership of the head of madrasah, particularly in continuous planning, organizing, implementing, and supervising administrative processes, as well as in empowering educational personnel and effectively integrating information technology to establish an orderly, transparent, and accountable administrative system